ON THE DOLICHOPODIDAE (DIPTERA: EMPIDOIDEA) FROM SERBIA (Acta Entomologica Serbica, 2016)
The data on Dolichopodidae from Serbia are reviewed. New records resulting from short-term visits to Serbia in 2014 and 2015 are presented. Of the 24 species collected, 14 are recorded for the first time for Serbia. The other known species are listed, and the number of reliably reported species from the country has reached 37 species belonging to 19 genera. Almost all collected species are widespread across the Palaearctic Region or across Europe